Evaluation of Blended NPS Fertilizer Rates and Inter Row Spacing on Yield Components and Yield of Maize (Zea Mays L.) - Abduraman Nure; Husen Aman Jara (Iraqi Journal of Industrial Research)
Corn is an important cereal crop in Ethiopia due to its use as a source of food security. However, its productivity is limited by insufficient application of the NPS fertilizer and different row spacing. A field trial was carried out to assess the effects of the application of different NPS fertilizer quantities and inter row spacing on the growth, yield components and yield of maize and the cost-benefit analysis of the NPS compound fertilizer application on the yield of maize in the main growing season 2019/2020.The study was arranged in a factorial combination of five levels of NPS fertilizers (0, 50, 100, 150 and 200 kg NPS ha-1) and four inter row spacing (55 cm, 65 cm, 75 cm and 85 cm). in a randomized complete block design with three replications. The consequence showed the main result of the NPS fertilizer had a highly significant (p <0.01) effect on days up to 50% anthesis, days up to 50% silk formation, 90% physiological maturity, leaf area, leaf area index, number of plants at harvest, the number of grains per ear was determined from the main effects of NPS fertilizer of 200 kg NPS ha-1. The interaction effects of NPS and row spacing have highly significant (p <0.01) effects on the number of ears per plant, number of ears per hectare, ear length, agronomic effectiveness and grain yield were obtained when using 150 kg. measured NPS ha-1 at 75 cm row spacing. The highest economic (91,608 Birr ha-1) and a higher MRR (1745%) resulted from the 150 kg NPS ha-1 and 75 cm row spacing. Thus, it should be noted that the application of 150 kg NPS ha-1 with a row spacing of 75 cm was both agronomic and cost-effective for the grain yield of the Melkassa-II in the study area.